The academic discourse socialisation challenges and coping strategies of international graduate students entering English-medium universities. (November 2018) - Wette, Rosemary; Furneaux, Clare
Abstract: The internationalisation of higher education and current dominance of academic English has led to a significant growth in the number of international students studying in English medium universities. The University of Reading in the United Kingdom and the University of Auckland in New Zealand are two such universities, and they provide the settings for this study. While research to date has given us insights into the psychological and socio-cultural challenges faced by these students, their academic discourse socialisation difficulties have attracted less research attention. Drawing on data from narrative frames and interviews, this study explored aspects of the academic discourse socialisation of 31 incoming international graduate students from 20 countries. We found many commonalities in students' reports of their previous experience and the difficulties they were facing, including their unfamiliarity with aspects of source-based, critical, and writer-responsible writing, and self-perceived inadequacies regarding their knowledge of discipline-specific academic vocabulary, metadiscourse strategies, and the ability to compose concise, coherent texts. However, students also reported developing independent learning strategies and identifying useful sources of advice and support. Participants' reflections revealed a self-critical appreciation of and sense of responsibility for overcoming their difficulties, and a determination to achieve success in their studies.